Thulium laser in interventional endoscopy: animal and human studies - Tontini, Gian E.; Neumann, Helmut; Pastorelli, Luca; Spina, Luisa; Cavallaro, Flaminia; Soriani, Paola; Rimondi, Alessandro; Bruni, Barbara; Clemente, Claudio; Fagnani, Filippo; Lagoussis, Pavlos; Carmignani, Luca; Vecchi, Maurizio (Endoscopy, 2017)
Background and study aims The thulium laser system (TLS) is an emerging surgical tool. The 2-μm wavelength provides a confined coagulation depth (0.2 – 0.4 mm) to reduce the potential for inadvertent injuries. For the first time ever, we assessed TLS feasibility for endoscopic hemostasis ex vivo in pigs. In addition, we performed the first in vivo hemostatic treatments in humans.Patients and methods Tissue damage induced by TLS using different settings and optical fibers was compared to that from argon plasma coagulation (APC) in established ex vivo animal models. Three consecutive patients with complex nonvariceal upper gastrointestinal bleedings were treated and followed up.Results No deep submucosal injury was observed in animal models. The TLS showed a progressive penetration depth with increased power outputs and tissue exposures but very limited vertical tissue injury (0.1 – 2.0 mm) and lateral spreading damage (0.1 – 0.3 mm and 0.2 – 0.7 mm using the 365-µm and 550-µm fibers, respectively). In vivo, endoscopic hemostasis with TLS was always successful without complications.Conclusions The TLS has proven to be very precise and easy to use. This novel technique appears to be a promising tool for advanced interventional endoscopy.